(untitled) (Research, Society and Development, 2020)
The diachronic relationship between space and time is the central topic of this research. The city is not a closed, immutable, and permanent body whose structure reveals a solid constancy, but an open body, a catharsis of time that in its course is metamorphosed, from those who occupy, inhabit and circulate through it. Consequently, the constant transformations or conservation in the urban landscape of the city directly reflect on the historical, mnemonic and identity relationships of the inhabitants with the image, aesthetics and city structure. In view of these constant transformations in space-time, this article aims to present some propositions about pedagogical practices in teaching art that use the process of urban displacement as a propellant of sensitive experiences to the student, capable of awakening a poetic look on the city. For this, the methodological path described is of a qualitative nature, investigating the perceptions of students in the city, materialized by their poetic and imagery records. In this way, the phenomenological approach to understand the data pointed out that the referred pedagogical practice of urban displacement made it possible to approach and expand the contact of students with the different city spaces Inciting in them a sensitive poetic look at the aesthetic and urban structure.